2011
DOI: 10.1111/j.1469-8986.2011.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Responsibility modulates neural mechanisms of outcome processing: An ERP study

Abstract: The role of personal responsibility in decision-making and its influence on the outcome evaluation process have been investigated relatively rarely in cognitive neuroscience. The present event-related brain potential (ERP) study manipulated the subjective sense of responsibility by modifying outcome controllability in a gambling task. Participants reported a higher sense of responsibility and produced a larger fERN when they were told that the game was 'controllable' compared with when they were told that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 12 publications
2
62
0
1
Order By: Relevance
“…nonrandom) [14], and appears only if the response is produced before, rather than after, the prediction is made [13]. Further, the sense of personal responsibility over choice behavior seems to be a critical factor underlying this process [24].…”
Section: Discussionmentioning
confidence: 98%
“…nonrandom) [14], and appears only if the response is produced before, rather than after, the prediction is made [13]. Further, the sense of personal responsibility over choice behavior seems to be a critical factor underlying this process [24].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, converging neuroscientific evidence points toward highly interconnected networks of brain regions underlying cognitive-emotional behaviors (Pessoa, 2009). Hence, it is reasonable to assume a tight and reciprocal relation between agency and affective processes: On the one hand, self-agency may enhance the value of action outcomes (Bednark, Reynolds, Stafford, Redgrave, & Franz, 2013;Li, Han, Lei, Holroyd, & Li, 2011) and, vice versa, the reward value of an outcome may modulate sense of agency over that outcome.…”
mentioning
confidence: 99%
“…Crucially, when the participants’ actions were unrelated to the occurrence of the sensory event, we observed an enhancement in the fCRP response in PD patients compared to age-matched controls. As highlighted in the Introduction, previous studies have demonstrated that the fCRP response is enhanced by the perceived responsibility over Li et al (2011) and coupling of an intentional action with a sensory event (Bednark et al, 2013; Bednark and Franz, 2014). Additionally, it has been previously demonstrated that PD patients on regular dopamine treatment perceive actions and sensory events as occurring closer in time than when OFF dopamine treatment (Moore et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Related to action, previous work has shown that the fCRP response to salient outcomes is enhanced when participants have a sense of control over the salient outcome (Li et al, 2011; Bednark et al, 2013; Bednark and Franz, 2014). Conversely, the novelty P3 is thought to reflect the engagement of evaluative processes necessary for learning when a novel stimulus is encountered (Friedman et al, 2001; Jongsma et al, 2006; Sailer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%